Asuhan Kebidanan Continuity Of Care (COC) Pada Ibu Hamil dengan Ketuban Pecah Dini, Nifas, Bayi Baru Lahir dan Keluarga Berencana Pada Ny. T di Klinik Dawiyah Binjai Kabupaten Langkat Provinsi Sumatera Utara - Pratiwi, Aisyah; Lisnur Sinaga; Pasaribu, Lasmaro; Saragih, Ijah; Damanik, osdiana; Manurung, Herna Rinayanti; Wahyuni, Retno (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2021)
The picture of MMR in Aceh from 2015 to 2019 has fluctuated in the last five years, in 2019 it increased to 172 per 100,000 live births. Mrs. D was one of the patients who was on a pregnant visit, when the authors conducted the initial survey. Purpose: this study was to conduct Continuity Of Care (COC) Midwifery Care for Mrs. D starting from Pregnancy, Maternity including BBL, Postpartum, Family Planning at Dawiyah's Certified Practice Midwife in 2020/2021. Method: This research is a type of research used is descriptive with a case study approach. The subjects in this study were Mrs. D G1P0A0 9 weeks gestational age up to family planning acceptors. Result: After carrying out a case study of continuous care (COC) on Mrs. D from pregnancy to postpartum and family planning as well as BBL care, where Mrs. D's pregnancy is a physiological pregnancy, Mrs. D's delivery is spontaneous vaginally. Mrs. D's involution postpartum period was normal, Mrs. D's baby was normal, there was an increase in weight according to age, there was no infection in the umbilical cord and the baby was exclusively breastfeeding, postpartum family planning, Mrs. D and her husband chose MAL, it is known that sustainable care is effective in preventing both morbidity and mortality. Suggest: the Practice Midwife Dawiyah to maintain the quality of midwifery services or care for pregnant women, maternity, newborns, and perform midwifery care in accordance with existing theory.